(untitled) (Journal of the College of Basic Education, 2022)
1- Building a training curriculum using compound exercises that are compatible with the capabilities of the research sample.2- Learn about the effect of the training curriculum for developing special endurance in some of the skillful abilities of young footballers.In order to achieve the objectives of the research, the researchers put the following hypotheses:1. There are statistically significant differences between the results of the pre and post tests of the control and experimental groups in football endurance and some skill.2. There is a discrepancy in the rates of development in endurance and some football skills.